PENGARUH SELF EFFICACY DAN KOMITMEN ORGANISASI TERHADAP GOAL ORIENTATION KARYAWAN PADA PT. KERTA RAJASA RAYA KABUPATEN SIDOARJO - DIAN SYAFITRI, HERWIN (Jurnal Ilmu Manajemen (JIM), 2018)
The development of the global industrial era makes the business world in Indonesia became more and more rapidly.This makes the more companies that pitch, so the more rigorous competition antra corporate also achieved its goal.When a company wants to compete in the speed of growth of the business, then the company should pay attention tothe human resources (HR) or employees like self efficacy, goal orientation, and the commitment of employees toassist the company in achieving destination. The purpose of this research was to test and analyze the effect of selfefficacy and organizational commitment towards goal orientation employees at PT Kerta Rajasa Raya Sidoarjo.This research is quantitative research the number of samples that used as many as 45 people. Measuring instrumentused in this research is the interview, observation, and a detailed questionnaire. Data analysis using the techniquesof analysis of Partial Least Square (PLS) with the help of SmartPLS 3.0 software and Statistical Package for theSocial Science (SPSS). This research uses the scale likert scale as the measurement. The results show that thepositive effect of self efficacy and significantly to goal orientation, while the Organizations commitment to apositive and influential not significant toward the goal of employee orientation. Keywords: Self Efficacy, Organizational Commitment, Goal Orientation